GENOTYPE CHARACTERIZATION OF Leishmania (Viannia) braziliensis ISOLATED FROM HUMAN AND CANINE BIOPSIES WITH AMERICAN CUTANEOUS LEISHMANIASIS - Lasaro Teixeira Ferreira; Aparecida Helena de Souza Gomes; Vera Lúcia Pereira‐Chioccola (2015)
Introduction: American tegumentary leishmaniasis (ATL) can be caused by Leishmania (Viannia) braziliensis complex. The evolution of ATL initially results in lesions and can develop into disseminated or diffuse forms. The genetic diversity of L. (V.) braziliensis in some endemic areas of Brazil has been poorly studied, such as in the state of São Paulo. This study analyzed the genetic diversity of L. (V.) braziliensis isolates collected from patients and dogs with LTA from the state of São Paulo. Methods: Leishmaniasis diagnosis was determined by PCR. The 132 biopsies were collected in different regions of Sao Paulo State, Brazil (36 municipalities). The genetic characterization of L. (V.) braziliensis isolates was tested by RFLP-PCR using DNA extracted from biopsies. The primer set amplified a specific region of Leishmania internal transcribed spacers of the ribosomal DNA locus. Results: Of the 132 samples, 52 (40%) were completely genotyped by RFLP-PCR (44 from human patients and eight from dogs). The results showed nine distinct patterns. The majority of the genotyped samples were from Sorocaba (30), and the others were distributed among 14 other municipalities. The first pattern was more frequent (29 samples), followed by pattern 2 (nine samples) and pattern 3 (three samples). Patterns 4, 6, 7, 8 and 9 were composed of two samples each and pattern 5 of one sample. Conclusion: These results suggest that polymorphic strains of L. (V.) braziliensis circulate in the state of São Paulo. These data agree with studies from other regions of Brazil, showing great variability among the natural populations of endemic foci.